ANALISIS FAKTOR PENERIMAAN DAN PENGGUNAAN TEKNOLOGI DALAM SISTEM INFORMASI AKUNTANSI DENGAN PENDEKATAN TAM - Armanda, Ribka; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the receiving factors and the utilization of technology in the Accounting Information System which has been done by using the Technology Acceptance Model (TAM) approach, which is represented by the test of influence of exogenous constructs i.e.:business process support, management support, and flexibility system support to the endogenous constructsi.e.: perceived of behavioral intention, perceived of attitude towards using, perceived of usefulness and perceived ease of use.The samples have been selected by using purposive random sampling, the research instrument has been carried out by issuing questionnaires to 125 respondents who are the employees of Shipping Cargo Expedition in Surabaya that uses AIS in daily work. The data is analyzed by using partial least square.The results of the research shows i.e.: (1) the support to the business process, flexibility system and perceived ease of use have positive influence to the perceived of behavioral intention in using the technology in AIS. Meanwhile, the management support and perceived of usefulness do not have any positive influence to the perceived of behavioral intention in using the technology in AIS. (2) Business process support, management support and the perceived of usefulness have positive influence to the perceived of attitude toward using of technology in AIS. Meanwhile, the perceived of behavioral intention, flexibility system support, and the perceived ease of use do not have any influence to the perceived of attitude towards using of technology in AIS. (3) Business support system, flexibility system support, and perceived ease of use have positive influence to the perceived of use of technology in AIS whereas the management support does not have any positive influence to the perceived of use of technology in AIS. (4) Business process support, flexibility system support, and management support have positive influence to the perceived easeof use of technology in AIS. Keywords:Technology Acceptance Model, Partial Least Square, Accounting Information System